Short-Term Effects of Pacifier Texture on NNS in Neurotypical Infants. (29th April 2013) - Oder, Austin L.; Stalling, David L.; Barlow, Steven M.
Abstract : The dense representation of trigeminal mechanosensitive afferents in the lip vermilion, anterior tongue, intraoral mucosa, and temporomandibular joint allows the infant's orofacial system to encode a wide range of somatosensory experiences during the critical period associated with feed development. Our understanding of how this complex sensorium processes texture is very limited in adults, and the putative role of texture encoding in the infant is unknown. The purpose of this study was to examine the short-term effects of a novel textured pacifier experience in healthy term infants (N = 28 ). Nonnutritive suck (NNS) compression pressure waveforms were digitized in real time using a variety of custom-molded textured pacifiers varying in spatial array density of touch domes. MANCOVA, adjusted for postmenstrual age at test and sex, revealed that infants exhibited an increase in NNS burst attempts at the expense of a degraded suck burst structure with the textured pacifiers, suggesting that the suck central pattern generator (sCPG) is significantly disrupted and reorganized by this novel orocutaneous experience. The current findings provide new insight into oromotor control as a function of the oral somatosensory environment in neurotypically developing infants.